Effect of Temperature Shock on the Triploidization Success of Seurukan Fish (Osteochilus vittatus) - Eriani, Kartini; Syahrin, Alfis; Muchlisin, Zainal Abidin (Biosaintifika: Journal of Biology & Biology Education, 2017)
Seurukan fish (Osteochilus vittatus) has many advantages, besides the fish also has disadvantages which are the slow growth, so the temperature shock of triploidization technique was expected to solve the problem. The objective of the present study was to obtain an effective temperature to increase of triploidization success of seurukan fish (Osteochilus vittatus). The experimental method and completely randomized design model were used in this study. Five levels of temperature shocks at three replicates were tasted: 4? (cold), 6? (cold), 28? (normal), 35? (heat) and 37? (heat). The sperms and eggs were fertilized in the plastic jar then a total 100 of fertilized eggs (zygotes) were taken randomly 3 minutes after fertilization and soaked in respective temperature for 90 seconds, and then incubated in incubation jars at the water temperature of 28-29?. The results showed that the temperature shock gave the significant effect on the hatching and the success of triploidization success (P?0.05), but did not give the significant effect the fertility and survival rates (P>0.05). The triploid fish can be achieved using cold and heat shock, but the higher triploid fish was recorded at 37? was the best temperature recommended for triploidization of Seurukan fish.